Report of the Steering Group on Science and Technology for the Formulation of Eighth Five Year Plan (1990-95) - Planning Commission (Planning Commission, 1989)
The most important motive force for dynamic change, other than the human spirit, is the application of science & technology in all spheres of developmental activity. There have been many efforts to work out the precise contributions of labour, capital and technology to growth; and what has emerged very clearly is that technology accounts for most of economic growth.
Planning Commission Government of India
Planning Commission Government of India